Analysis of The Effect of Village Fund, Allocation of Village Fund, Shopping of Grants of School Operational Assistance Funds, and Human Development Index on District Poverty Level in Central Java Province 2018-2020 - Pertiwi, Ika Mahardika Endah; Arif, Muhammad (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Poverty is a problem faced by every country, including Indonesia. The percentage of poor people in Indonesia is still concentrated in rural areas. The government seeks to reduce inequality between regions, Village Funds, Village Fund Allocations, and School Operational Assistance Grant Expenditures are one of the programs made by the government to reduce inequality and poverty. The purpose of this study was to analyze the effect of the Village Fund, Village Fund Allocation, School Operational Assistance Grant Expenditure and the Human Development Index to reduce district poverty levels in Central Java Province. This research is quantitative in nature using secondary data in the form of panel data from 2018-2020 processed with the EViews 10 program. The results show that the Village Fund has a negative and insignificant effect on reducing poverty with a coefficient value of -28,266. Allocation of Village Funds has a negative and significant effect in reducing poverty with a coefficient value of -955,748. School Operational Assistance Grant Expenditure has a negative and significant effect in reducing poverty with a coefficient value of -3.477. The Human Development Index has a negative and significant effect on reducing poverty with a coefficient value of -0.229.